Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1159/000007744
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Patterns of Crohn’s Disease in Greece: A Follow-Up Study of 155 Cases

Abstract: The aim of this prospective study was to elucidate the clinical features and natural history of Crohn’s disease in Greece. One hundred and fifty-five Greek patients with definite diagnosis of Crohn’s disease were followed-up for a mean period of 9.7 years and evaluated for clinical patterns and course of illness. The male/female ratio was 1.58:1. The peak incidence of the disease was observed between 20 and 30 years of age. The majority of patients were urban dwellers and of higher socio-economic level compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 40 publications
(47 reference statements)
1
17
0
8
Order By: Relevance
“…So, Maeda et al [46] found that out of 203 Japanese CD patients, 21 had arthritis (10.3%) and 3 had spondylitis (1.5%). Triantafillidis et al [47] reported a frequency of 30% of arthritis/arthralgias in a cohort of 155 Greek CD patients. The study by Bernstein et al [48] from Canada was based on the ICD code from hospitalized patients with IBD reporting a 4% prevalence of AS with male CD patients being more frequently affected than male UC patients.…”
Section: Epidemiologymentioning
confidence: 99%
“…So, Maeda et al [46] found that out of 203 Japanese CD patients, 21 had arthritis (10.3%) and 3 had spondylitis (1.5%). Triantafillidis et al [47] reported a frequency of 30% of arthritis/arthralgias in a cohort of 155 Greek CD patients. The study by Bernstein et al [48] from Canada was based on the ICD code from hospitalized patients with IBD reporting a 4% prevalence of AS with male CD patients being more frequently affected than male UC patients.…”
Section: Epidemiologymentioning
confidence: 99%
“…Do mesmo modo, as manifestações clínicas da DC e da RCUI nos casos da presente série, bem como os relativos à localização anatômica das lesões inflamatórias não diferem das descrições publicadas (10,11,26) . Deve ser registrada, porém, a virtual ausência de pacientes com retite ou proctite isoladas.…”
Section: Gravidade Das Doenças E Fatores Envolvidosunclassified
“…C r o h n's d i sea se (C D ) i s a ch r o n i c i n f l a m mator y disease of unknown etiology that may affect any level of the gastrointestinal tract [1][2][3] . It is well established that immunological mechanisms are involved in the pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 99%